Kilka uwag o finansowych aspektach funkcjonowania polskiej służby zagranicznej w latach 1776-1792 - Anusik, Zbigniew (Acta Universitatis Lodziensis. Folia Historica, 1999)
The article concerns financial matters of Polish foreign service’s activity in times of king Stanisław August Poniatowski, including a period of the Rada Nieustająca (Permanent Council) 1776-1788, as well as, a period of the Sejm Czteroletni (Great Sejm) 1788-1792. Results of research confirmed a view that both rise and drop of expenses for diplomatic service were depended on a scale of foreign activity of Poland. According to the author, total expenses fог foreign affairs can be estimated on 4262000 zł (1788-1792). It should be noticed, rise of those expenses exceeded total rise of budget expenses in Poland during the Sejm Czteroletni. In conclusion the ways of financial support for Polish diplomatic service are discussed, including an involvment of Polish diplomats in that activity as well as ideas of preparing new staff for Polish foreign service. All these issues seem to be open fields for future research exploration.